The impact of Hamas on the path of the Palestinian cause. - Ahmed, bida Mahmoud; Karim, Firdaus Abdul Rahman (Al-Adab Journal, 2015)
After Hamas took over the Palestinian government and chose to chair Mr. Ismail Haniyeh, took Israel besiege us with the help of international and European powers, which saw that Hamas is a terrorist movement, even came democratic process saw the validity of many international observers, and has taken the besieged various forms including what is political and some of which is economic, Israel focused on the second side, preventing a what was coming from Kmarkip Palestinian Authority money and delayed because of these arbitrary actions of staff Palestinians pay a lot, which led to mass protests were accompanied by violence between supporters of Fatah and Hamas later developed into bloody clashes claimed the lives of many dead, especially after the formation of the Hamas government tried to separate from the security forces formed by Fatah when it was in power security force. That the current situation in the territory of self-governing authority, including the most prominent of the many disadvantages of internal disunity and bickering between Fatah and Hamas, and the continuation of the Israeli aggression, will impact on the future of the Palestinian entity. Accordingly, any vision for the future will be fraught with the dangers of uncertainty so that the situation in the movement of change going on.